Ordering creativity? Knowledge, creativity, and idea generation in the advertising industry. (30th March 2006) - Nov, Oded; Jones, Matthew
Creativity and knowledge are closely linked. Recent research into the relations between them highlights social and organisational aspects. However, creativity seems difficult for ordering, and creative processes often involve people with different knowledge bases, requiring the integration of different types of knowledge. While the management of creativity in organisations is seen as a complex task, organisations do try to order creativity. The issue of how organisations do it is addressed in this paper by drawing on evidence from the advertising industry. Findings are presented from case studies of work practices of two large advertising companies. A number of processes and practices are identified that help manage and control creativity effectively. Based on these findings, a model of the inter-relations among knowledge, creativity and social interaction is developed. The model may be useful in gaining insight into the general case of knowledge sharing and innovation in knowledge-intensive organisations.